2010
DOI: 10.1590/s1984-82502010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oxidative stress and diabetic osteopenia in premenopausal rats

Abstract: The relationship between lipid peroxidation, antioxidant defense and diabetic osteopenia remains unclear. This study evaluated the relationship among lipid peroxidation index, antioxidant defense parameters and bone metabolism in a premenopausal diabetic model using measures including thiobarbituric acidreactive substances concentration (TBARS) and reduced glutathione (GSH) content in brain homogenates, histomorphometric analysis, biomechanical testing and bone mineral density (BMD). Female Wistar rats with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In contrast, the bone loss observed in the T1DM group, which did not receive insulin therapy, supports the anabolic effect of this hormone. In addition, a positive correlation between hyperglycaemia and TbSp and an inverse correlation between hyperglycaemia and BAr were observed in the T1DM group, reinforcing the previous results on the deleterious effects of high blood glucose on the bone tissue [10,14,[27][28][29].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, the bone loss observed in the T1DM group, which did not receive insulin therapy, supports the anabolic effect of this hormone. In addition, a positive correlation between hyperglycaemia and TbSp and an inverse correlation between hyperglycaemia and BAr were observed in the T1DM group, reinforcing the previous results on the deleterious effects of high blood glucose on the bone tissue [10,14,[27][28][29].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, for Rptorob -/mice, HFD feeding resulted in significantly higher trabecular and cortical bone thickness (while trabecular number showed a trend toward reduction) in the proximal tibia compared to the CD-fed mice. A previous study reported a correlation between trabecular thickness and systemic glycemic levels (61) . Therefore, it is possible that some of the bone phenotypes, observed in the HFD-fed Rptorob -/mice, are due, in part, to the protective metabolic phenotypes of deleting Rptor in bone (i.e.…”
Section: Bone Phenotypesmentioning
confidence: 96%